Role of N6-Methyladenosine RNA Modification in Cardiovascular Disease - Song, Dandan; Hou, Jianhua; Wu, Junduo; Wang, Junnan (Frontiers in Cardiovascular Medicine, 2021)
Despite treatments being improved and many risk factors being identified, cardiovascular disease (CVD) is still a leading cause of mortality and disability worldwide. N6-methyladenosine (m6A) is the most common, abundant, and conserved internal modification in RNAs and plays an important role in the development of CVD. Many studies have shown that aabnormal m6A modifications of coding RNAs are involved in the development of CVD. In addition, non-coding RNAs (ncRNAs) exert post-transcriptional regulation in many diseases including CVD. Although ncRNAs have also been found to be modified by m6A, the studies on m6A modifications of ncRNAs in CVD are currently lacking. In this review, we summarized the recent progress in understanding m6A modifications in the context of coding RNAs and ncRNAs, as well as their regulatory roles in CVD.